Analysis of the electrostatic field distribution in the hemispherical internal cell of radon monitors to estimate the collection efficiency of Po-218. (16th December 2021) - Fan, Z.; Xie, L.; Mo, Y.; Lin, F.; Hu, T.; Yuan, H.; Tan, Y.
Abstract: The collection efficiency of the hemispherical internal cell of radon monitors depends on many factors, with the distribution of the electric field and the relative humidity of the air being particularly important. COMSOL is used to simulate an internal cell with a plastic upper surface. Simulation results show a relatively uniform gradient of the electric field. Assuming that the electric field felt by the positively charged Po-218 ions in the internal cell is a linear function of its radial coordinate, a mathematical model of the collection efficiency is proposed. From this model, we obtained the following: 1) under the same neutralization rate and potential, the electric field gradient has little effect on the collection efficiency; 2) under the same neutralization rate, the collection efficiency increases with the potential on the cell wall. If the neutralization rate is small, then the potential value for the maximum collection efficiency is also small. At a relative humidity of 6%–10%, the collection efficiency saturates for values of the electric potential on the cell wall larger than 5 kV; 3) under the same potential, a large neutralization rate corresponds to reduced collection efficiency. At high potential, the collection efficiency is relatively less affected by the neutralization rate. Higher collection efficiency can be achieved under high potential and low humidity conditions. This study provides a theoretical foundation to design the internal cell of radon monitor for improving the collection efficiency of Po-218.